(untitled) (Eurasian Journal of Engineering and Technology, 2025)
This paper proposes a solution for building a 3D scanning system using Arduino and MATLAB. VL53L0X laser distance sensors are mounted on a car steering wheel to generate a 3D point cloud of the surrounding object surfaces. The system operates in real time and visualizes the data through a MATLAB interface. This method enables accurate, stable, and straightforward digitization of shapes using simple components. The proposed solution is low-cost, reprogrammable, and applicable in various fields, including robotics, automotive engineering, and manufacturing technologies